PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V MIN 9 PIDIE - Junaidah; Chairatul Munawwarah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
This study aims to determine the application of the Problem Based Learning model in improving student learning outcomes in 5th grade MIN 9 Pidie. The research design used is Classroom Action Research (CAR) Kemmis and Taggart model design with 3 cycles. Data collection techniques used in this study were observation, tests, and documentation. Data analysis techniques used qualitative and quantitative. The subjects in this study were 31 students in class V-C MIN 9 Pidie consisting of 15 male students and 16 female students. In cycle I, the average score was 66.19 with a percentage of 41.94%. In cycle II, the average score was 77.61 with a percentage of 70.97%. And in cycle III, the average score was 89 with a percentage of 100%. The results of this study indicate that the application of the Problem Based Learning model can improve student learning outcomes in class V-C MIN 9 Pidie